Corporate Reputation as a Mediator Between Environmental Awareness and Brand Transparency Toward Social Sustainability in Indonesia’s Beauty Industry - Cellica Jolie; Ryan Putra Panjaya; Elda Elda; Noviana Krisnawati (Lembaga Pengembangan Kinerja Dosen, 2025)
This research explores the role of corporate reputation as a mediator between environmental awareness and brand transparency toward social sustainability in Indonesia's beauty industry. With growing consumer expectations for brands to align with environmental and social causes, this study examines the impact of environmental awareness and perceived brand transparency on social sustainability through corporate reputation. A quantitative research approach is employed using multiple regression analysis and Sobel tests on data from Indonesian beauty product consumers. The findings reveal that while perceived brand transparency positively affects corporate reputation, environmental awareness does not directly influence reputation or social sustainability. Additionally, corporate reputation does not mediate the relationship between environmental awareness, brand transparency, and social sustainability. These results suggest that transparency enhances brand reputation but does not automatically translate to social sustainability perceptions. The study recommends further research on additional mediators and practical strategies for companies to implement impactful social sustainability practices